(untitled) (Educational Dimension, 2023)
This research aims to refine the model of blended learning in higher technical education institutions using cloud-based information and communication technologies (ICTs). The study objectives include determining the role of cloud technologies among contemporary ICTs, analyzing the utilization of cloud technologies in traditional, online, and blended learning, and augmenting the blended learning model with mobile and cloud technologies. The research focuses on the implementation of ICTs in the higher education system of Ukraine. The subject of investigation encompasses the use of cloud technologies and other ICT learning tools in traditional, online, and blended learning. The research methods employed involve analyzing educational programs, monographs, dissertations, articles, conference materials, and online resources. Additionally, targeted pedagogical observations, interviews with educators and students, and analysis of teachers’ practical experiences are conducted. The findings emphasize that among various ICTs available for instructional purposes, cloud technologies stand out as facilitators of harmonious integration between the components of traditional education and technology-mediated learning. A promising approach to organizing the learning process, referred to as blended learning, involves the integration of traditional, distance, electronic, mobile, and cloud technologies. The study explores the model of blended learning in higher mathematics education for students in technical institutions, leveraging innovative ICTs. The primary conclusions and recommendations highlight the prevailing trend of transitioning towards blended learning in higher education and the need for further development of cloud technologies in instructional settings. Cloud technologies are particularly valuable for fostering student autonomy, enabling distance learning, and facilitating collaborative research, thereby supporting ongoing monitoring of learning outcomes and timely adjustments to optimize learning experiences.